Firm dominance in EU competition law the competitive process and the origins of market power - Marcos Ramos, Jorge (International competition law series ;, 2020)
Firm Dominance in EU Competition Law' explores the role of dominant firms in the competitive process, proposing that conduct should be scrutinized differently depending on the source of market power, rather than using the same approach for all dominant undertakings. There have been various high-profile investigations at national, international, and supranational levels, with the complexity of the tech issues adding to the many questions about effective enforcement. This has led to an increased focus on the effectiveness of rules intended to prevent abuse of dominance. How does it come about that a certain firm dominates a market? Can an understanding of this process lead to more effective enforcement of competition law? That is the question approached in this compelling book. The author reviews the European Union's (EU's) Article 102 case law, comparing it with United States (U.S.) provisions, demonstrating that new ways of looking at market power are needed-- today's tech giants differ from older monopolies.